Molecularly imprinted ionic liquid magnetic microspheres for the rapid isolation of organochlorine pesticides in environmental water. Issue 7 (22nd February 2016) - Qiao, Fengxia; Gao, Mengmeng; Yan, Hongyuan
Abstract : A new type of molecularly imprinted ionic liquid magnetic microspheres was synthesized by aqueous suspension polymerization, using 4, 4′‐dichlorobenzhydrol as a dummy template, and 1‐allyl‐3‐ethylimidazolium hexafluorophosphate and methacrylic acid as co‐functional monomers. The results of morphology and magnetic property evaluation of the obtained microspheres demonstrated that it was monodispersed spherical, possessed a rough surface, and an outstanding magnetic properties. Binding experiments revealed that it had a substantial adsorption capacity and strong recognition ability to organochlorine pesticides (OCPs) in aqueous solution. Then the microspheres were applied as an adsorbent of magnetic dispersive solid‐phase extraction for the selective recognition and rapid determination of OCPs in environmental water. Under the optimum conditions, good linearity of the three types of OCPs (dicofol, tetradifon, and p, p ′‐dichlorodiphenyldichloroethane) was achieved in the range of 1.0–100 ng/mL ( r ≥ 0.9994). The recoveries at three spiking levels ranged from 82.6 to 100.4% with the RSDs less than 6.9%.